Language Politeness in the Tradition of Speech Begalan Banyumas Marriage Customs - Mumpuni, Atikah (Peneliti.net, 2024)
Begalan is a typical tradition in marriage customs in Banyumas Regency. The tradition of begalan involves a lot of dialogue in it which is loaded with values of advice. However, the forms of politeness in the begalan tradition have not been studied much. This study aims to describe the politeness of the language used by begalan players in traditional marriage ceremonies in Banyumas Regency. This research is a content analysis research, the data analyzed for language politeness is in the form of a video of the begalan procession. The data analysis stage used refers to the Krippendorff content analysis stage which consists of six stages, namely data collection, sampling, recording/recording, reduction, drawing conclusions, and describing results. The results of the study found that the begalan procession in traditional ceremonies in Banyumas was divided into two stages, namely the preparation stage and the implementation stage. In the preparation stage, the guide explained the purpose of the begalan event using the language of manners alus. Meanwhile, at the implementation stage, both players use Javanese ngoko with Banyumas dialect. The conclusion that can be written is that in the context of language politeness, whether carried out by guides or players, it is in harmony with language politeness. It's just that jokes made by players tend to pay less attention to language politeness